A numerical method for infiltration problems - Solekhudin, Imam (2014)
In this paper, an infiltration problem is considered. The problem involves time-independent flow from periodic channels in a homogeneous soil. A governing equation of the problem is the Richards equation. This equation can be studied more conveniently by transforming the equation to a modified Helmholtz equation using the Kirchhoff transformation, dimensionless variables and a Laplace’s transform. This modified Helmholtz equation may be solved numerically using a dual reciprocity boundary element method (DRBEM).